IMPROVING STUDENTS' READING COMPREHENSION THROUGH SMALL GROUP DISCUSSION TEACHING METHOD - Cindy Wangsa Putri; Regina Regina; Surmiyati Surmiyati (IKIP Siliwangi, 2024)
This study aims to improve the reading comprehension skills of Class 8C students at SMPN 01 Mempawah Hilir. This Classroom Action Research was conducted in two cycles. The research data were obtained by observation and measurement techniques by using field notes, observation checklists, and tests. The data collected from field notes and the observation checklist were analyzed using data condensation, data display, and conclusion drawing. The tests were analyzed by comparing the individual scores of the students from the first cycle to the scores in the second cycle to see the improvement in individual learning. Besides, the mean score and the percentage of classical learning completeness were also calculated to show students’ overall improvement. Classically, the mean scores of the test results in the first cycle increased from 83.12 to 91.48 in the second cycle. Meanwhile, the percentage of classical learning completeness increased from 68% in the first cycle to 96% in the second cycle. In addition, based on the observation, the students learned more actively and enthusiastically in the class. It can be concluded that the Small Group Discussion teaching method has improved the Class 8C students' reading comprehension.